Investigation of a COVID-19 Islamic boarding school cluster outbreak in Kokap District, Kulon Progo Regency 2021 - Rosadi, Ahmad (BKM Public Health and Community Medicine, 2021)
Background: Wednesday, April 14, 2021, the Kokap I Public Health Center received information that some students in Islamic boarding school X experienced symptoms of anosmia. The puskesmas epidemiologist investigated to confirm and describe the outbreak that occurred according to the variables of person, place, and time and find and control the disease. Method: This research used a descriptive design. Case definitions were students and boarding school administrators who have confirmed COVID-19 through AG and PCR tests. Researchers collected data in two ways: primary data obtained from interviews using a structured questionnaire according to the guidelines and secondary data, namely confirmation case data obtained from Kokap Health Center 1. Result: There were 68 confirmed cases of 134 students and boarding school administrators (Attack Rate = 50.75%), with 34% of the cases being men. The highest proportion of cases occurred at the age of 12-25 years (84%), the highest education level was in junior high school (47%), and the distribution of places mainly was in the Hargotirto area (24%). The predominant symptoms were anosmia (15%) and cough (10%). The Islamic boarding schools' conditions that caused the COVID-19 cluster were that the schools did not strictly enforce health protocols, students were allowed to go in and out, and boarding school administrators and teachers did not all live in the school area. The conditions of residence of Islamic boarding school students do not meet reasonable requirements. Conclusion: There was a COVID-19 outbreak at Islamic boarding school X on April 16, 2021, with the primary symptom of anosmia. The application of health protocols in social distancing could not be applied so that transmission occurred. Socialization and implementation of strict health protocols are essential to prevent similar incidents. Latar Belakang: Hari rabu tanggal 14 april 2021 puskesmas kokap I mendapatkan informasi bahwa sejumlah siswa pondok pesantren X mengalami gejala anosmia. Investigasi dilakukan oleh petugas epidemiolog puskesmas untuk mengkonfirmasi KLB tersebut. Tujuan penyelidikan KLB ini adalah mengkonfirmasi KLB, mendeskripsikan KLB, memberikan gambaran KLB yang terjadi menurut variable orang tempat dan waktu, menemukan dan melakukan pengendalian penyakit. Metode: Penyelidikan ini menggunakan rancangan deskriptif. Definisi kasus adalah siswa dan pengurus pondok pesantren yang terkonfirmasi COVID-19 melalui tes AG dan PCR. Pengumpulan data dilakukan dengan dua cara yaitu data primer yang diperoleh dari hasil wawancara dengan menggunakan kuesioner terstruktur sesuai pedoman dan data sekunder yaitu data kasus konfirmasi yang diperoleh dari Puskesmas Kokap 1. Hasil: Ditemukan sebanyak 68 kasus konfirmasi (Attack Rate= 50,75%) dari 134 siswa dan pengurus pondok pesantren. Sebanyak 34% kasus adalah laki-laki. Proporsi kasus paling banyak terjadi pada usia 12-25 tahun (84%), tingkat pendidikan paling tinggi pada SMP (47%), distribusi tempat paling banyak pada wilayah hargotirto (24%). Gejala dominan adalah anosmia (15%) dan batuk (10%). Kondisi pondok pesantren penyebab klaster COVID-19 adalah pondok pesantren tidak menerepkan protokol kesehatan dengan ketat, siswa diperbolehkan keluar masuk pondok pesantren, pengurus dan guru pondok pesantren tidak semuanya tinggal di dalam pondok pesantren, kondisi tempat tinggal siswa pondok pesantren belum memenuhi syarat yang baik. Kesimpulan: Terjadi sebuah KLB COVID-19 di pondok pesantren X pada tanggal 16 april 2021, gejala utama anosmia. Penerapan protokol kesehatan berupa social distancing tidak dapat diterapkan sehingga terjadinya transmisi. Sosialisasi dan penerapan protokol kesehatan yang ketat sangat penting dilakukan untuk mencegah kajadian serupa.